ANALISIS BIAYA OPERASIONAL TERHADAP KINERJA KEUANGAN PADA KANTOR KEMENTRIAN AGRARIA/BADAN PERTANAHAN NASIONAL KABUPATEN PINRANG - Fadillah, Nur (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
There are three types of costs, including personnel expenditures, goods expenditures, and capital expenditures after all are known. In 2017 the total employee expenditure decreased to Rp.3,624,448,248. This year is known to be lower than in other years, then increased in 2018 The total employee expenditure increased to Rp.7,693,123,816, Then in 2019 the total employee expenditure decreased again to Rp.6,970,178,455 and in 2020 the total personnel expenditures decreased again to Rp.6,676,347,465 although the amount of the decrease was not too significant. This study aims to determine the total operational costs each year, how much the budget and realization at the land office. From the totaled amount for a year, which was Rp. 89.75 in 2018 Rp. 95.52 in 2019 Rp. 93.53 and in 2020 it is Rp. 94.08. The data collection technique used is Observation and Documentation (data). Meanwhile, the data analysis technique used is descriptive qualitative analysis. The results showed that the financial performance of the land office was not significant because it could not manage personnel expenditures, goods expenditures, and capital expenditures.